The Influence of the Jurisprudential Inquiry Learning Model Assisted by Video Media on the Intellectual Skills and Learning Outcomes of Students - Tommy Prawoto, Jalu; Thang, Ha Va; Blazek, Vojtech (Indonesian Journal of Education Research (IJoER), 2023)
Purpose of the study: The aim of this research is to find out (1) whether there is a significant influence in the application of the jurisprudential inquiry learning model assisted by video media on students' intellectual skills. (2) is there a significant influence in the application of the jurisprudential inquiry learning model assisted by video media on student learning outcomes Methodology: The population in this study were all class XI high school students who were divided into 4 classes. The sampling technique is random sampling. The sample in this research was students in class XI social sciences 1 and XI social sciences 2, totaling 66 students. The research method used is an experimental research method. The research design used was Quasi experimental design with nonequivalent control group design. The data collection techniques used are observation and tests. The data analysis technique used was the one-way ANOVA test with a significance level of 0.5% Main Findings: The results of the research show (1) there is a significant influence in the application of the jurisprudential inquiry learning model assisted by video media on students' intellectual skills as evidenced by the mean comparison of 22.8888: 20.8056 tested using one way ANOVA with a significance level of 5% obtained Fobs > F table (7.98131106 > 3.07). (2) there is a significant influence in the application of the jurisprudential inquiry learning model assisted by video media on student learning outcomes as evidenced by the mean comparison of 10.1111: 8.1949 which was tested with one way ANOVA with a significance level of 5% obtained Fobs > F table ( 27.35758 > 4.56) Novelty/Originality of this study: This research uses a jurisprudential inquiry learning model assisted by video media, which combines a legal learning approach and the use of video media. This approach can be considered its latest, because it tries to combine two different elements to improve student learning. This can provide new insights into how to improve intellectual skills and learning outcomes through a combination of innovative learning models and media